2008
DOI: 10.1097/jcp.0b013e318172b8e6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Antipsychotics on Peptides Involved in Energy Balance in Drug-Naive Psychotic Patients After 1 Year of Treatment

Abstract: Weight gain has become one of the most common and concerning side effects of antipsychotic treatment. The mechanisms whereby antipsychotics induce weight gain are not known. It has been suggested that peptides related to food intake and energy balance could play a role in weight gain secondary to antipsychotic therapy. To better understand the pathophysiology of antipsychotic-induced weight gain, we studied the effects of 3 antipsychotic drugs (haloperidol, olanzapine, and risperidone) on peptides involved in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
2
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 35 publications
3
40
2
2
Order By: Relevance
“…28 In patients, increased levels of ghrelin have also been reported, especially after long-term treatment with OLA. [29][30][31][32] Furthermore, when BMI was taken into account, ghrelin levels of chronically treated patients were higher than would be expected for an untreated patient with the same BMI. 30,32 As ghrelin levels are known to be influenced by obesity levels, 33 this indicates that the effect of OLA on ghrelin levels is independent of weight gain.…”
Section: Discussionmentioning
confidence: 99%
“…28 In patients, increased levels of ghrelin have also been reported, especially after long-term treatment with OLA. [29][30][31][32] Furthermore, when BMI was taken into account, ghrelin levels of chronically treated patients were higher than would be expected for an untreated patient with the same BMI. 30,32 As ghrelin levels are known to be influenced by obesity levels, 33 this indicates that the effect of OLA on ghrelin levels is independent of weight gain.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, both of these two studies reported on total ghrelin levels only (Chen et al, 2011;Kim et al, 2008); while the three long-term studies reported on active ghrelin levels all indicated that SGAs can increase ghrelin levels (Murashita et al, 2007a;Murashita et al, 2005;Palik et al, 2005). Since acyl ghrelin (noctanoyl ghrelin) is the biologically active form of ghrelin which binds to the GHS-R1a receptor to exert its orexigenic effect (as mentioned earlier in section 2.1), it might be more relevant in the context of SGA-induced body weight gain compared to total ghrelin, although SGAs, as suggested by another study, also increase desacyl (inactive) ghrelin levels in the long-term (Perez-Iglesias et al, 2008). Together, these studies suggested that circulating ghrelin levels return to the levels of, or even above baseline after long-term SGA treatments.…”
Section: Longer Term Effects Of Sgas On Circulating Ghrelin Levelsmentioning
confidence: 98%
“…These findings are in accordance with an 8-week animal study which showed that 8 week of olanzapine, haloperidol or vehicle control treatments had no significant difference in circulating ghrelin levels in mice. Furthermore, the majority of longer-term studies reporting on ghrelin levels after more than 6 months of SGA treatments showed an upregulation effect of SGAs on circulating total (Esen-Danaci et al, 2008;Murashita et al, 2007a;Murashita et al, 2005), active (Murashita et al, 2007a;Murashita et al, 2005;Palik et al, 2005) or desacyl (Perez-Iglesias et al, 2008) ghrelin levels, with the exception of two studies (Chen et al, 2011;Kim et al, 2008) (see details in Table 1). Interestingly, both of these two studies reported on total ghrelin levels only (Chen et al, 2011;Kim et al, 2008); while the three long-term studies reported on active ghrelin levels all indicated that SGAs can increase ghrelin levels (Murashita et al, 2007a;Murashita et al, 2005;Palik et al, 2005).…”
Section: Longer Term Effects Of Sgas On Circulating Ghrelin Levelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Murashita et al reported that although there was weight gain by the 6th month of antipsychotic treatment, there was no significant difference in the serum adiponectin levels [13]. Perez-Iglesias et al reported a non-significant drop in serum adiponectin levels, although they did find a significant increase in the serum insulin and leptin levels and patient weight after one year of treatment with atypical antipsychotics [30]. Studies focused on the correlation of atypical antipsychotics with weight gain and insulin resistance have shown that occasionally there is no significant difference among the atypical antipsychotics and that Olanzapine and Clozapine have more involvement with weight gain and the disruption of glucose regulation [31][32][33][34] than other drugs.…”
Section: Discussionmentioning
confidence: 88%